Analyzing degradation of ore pass walls in Kiirunavaara mine using scanning data - Sredniawa, Weronika; Skawina, Bartlomiej; Garcia, Jorge Recio; Rapp, Joel (Frontiers in Built Environment, 2023)
Ore passes play a vital role in underground mining operations by facilitating the gravity-driven movement of ore from production levels to lower levels. Failure of the ore pass has serious consequences, including possible production disruptions and substantial financial investments in reconstruction or rehabilitation. Failure mechanisms are often associated with rock mass quality, stress conditions, and wear of the ore pass walls. This study investigated the degradation of ore pass walls using scanning data at LKAB's Kiirunavaara mine in Sweden. Geotechnical information obtained from various sources aided in further understanding the ore passes' conditions. The study revealed variations in the ore pass growth rates, highlighting potential stability concerns and the correlation between throughput and pass growth. The findings underscore the need for continuous monitoring and regular inspection to manage wall degradation. The paper proposes potential rehabilitation measures to ensure the stability and safety of ore passes in mining operations.